Six weeks of isometric resistance training led to evidence of corticospinal but not reticulospinal adaptation in previously untrained adult males - Simon Walker; Katherine E. J. Keogh; Meghan Tanel; Aidan S. W. Baker; Anne M. E. Baker; Dawson J. Kidgell; Stuart N. Baker (Experimental Brain Research, 2026)
The latest hypothesis regarding the source of enhanced neural activation from resistance training is the reticulospinal rather than the corticospinal tract, based on invasive animal and emerging human data. The present study employed a six-week isometric resistance training intervention in a randomized controlled design to address this knowledge gap. Thirty-nine healthy, untrained males (age ~23 y, sustained contraction group n = 13, explosive contraction group n = 9, control group n = 17) underwent neuromuscular and electrophysiological testing and completed all study requirements. Maximal isometric torque (MVC) and rate of torque development (RTD) were measured during a familiarization session as well as before and after the six-week period. Transcranial magnetic stimulation was used to assess motor-evoked potential (MEP) area and silent period duration while subjects contracted to 10% of MVC. Loud sound (120 dB) was used to modulate MEP area and reaction time to visual stimuli during the StartReact test. Only the intervention groups demonstrated significant improvements in MVC (27%) and RTD (60%) (both P < 0.01), along with reduced MEP area (− 21%) and silent period duration (− 23%) (both P < 0.01). The sustained contraction group showed reduced modulation of reaction time and increased MEP suppression due to loud sound. Short-term resistance training seemed to reduce cortical inhibition and corticospinal excitability in both training groups. The study showed conflicting changes in measures purported to evaluate reticulospinal functioning. It is recommended to examine different forms of resistance training and longer training exposure in future.

Intraoperative drug delivery to hindbrain tumours via an injectable hydrogel is well tolerated and confers survival benefit against atypical teratoid/rhabdoid xenografts - Cara Moloney; Phoebe McCrorie; Amr ElSherbeny; Harry Porter; Chiara Bastiancich; Hasan Slika; Aanya Shahani; Emre Derin; Esteban Velarde; Jackson Miller; John Theodore; Khushi Varshney; et al. (Drug Delivery and Translational Research, 2026)

Evaluating a structured expert elicitation approach for adaptive conservation management based on lessons from five years in practice - Helen J. Mayfield; James Brazill‐Boast; Mick Andren; Michiala Bowen; Adam Fawcett; Trent Forge; Luke Foster; Ross Goldingay; Paul Hillier; Meagan Hinds; Simon Lee; Erica Mahon; et al. (Conservation Biology, 2026)
Adaptive management of threatened species relies on having ex ante estimates of species’ responses to different interventions. Structured expert elicitation is often used to generate these estimates, but comparisons of these expert‐predicted outcomes with observed results are rare. This study aims to evaluate the utility of expert elicitation for adaptive management in the New South Wales Saving our Species program in Australia by revisiting six species management plans that were generated from tailored structured elicitation guidelines developed five years prior. Each species’ management plan included a defined scope, conceptual model, monitoring indicators, and estimated response to management curves under different scenarios. Experts reviewed the conceptual models after five years of management and compared the predicted response to management with observed monitoring data. In three of the six case studies, observed outcomes closely matched predictions. Where predictions diverged, factors such as unanticipated new threats and unexpected responses to interventions potentially contributed to discrepancies. However, in all cases, the structured approach provided a clear logic for planning, enabling managers to systematically refine their understanding. The conceptual models and response curves were valuable for collaborating, communicating, and generating hypotheses for unexpected results. This work demonstrates the value of tailored guidelines in supporting adaptive management processes and showcases the value of documenting expert knowledge in management settings with high uncertainty.

Swimming in urban estuaries: Understanding stormwater contamination events and recovery from historical data - Simon D. Lloyd; Josef I. Bisits; Gordana Popovic; Paul Osmond; David J. Roser; Stuart J. Khan (Water Research, 2026)

Cytoplasmic flow dynamics in arbuscular mycorrhizal fungi are intrinsic and independent of plant hosts - Malin Klein; Loreto Oyarte Gálvez; Daniel van der Lugt; Corentin Bisot; Simon van Staalduine; Stuart A. West; Vasilis Kokkoris; Lemeng Dong; Harro Bouwmeester; Thomas S. Shimizu; James T. Weedon; E. Toby Kiers (Fungal Biology, 2026)

Role of freshwater availability and terrestrial land‐cover change in the distribution of a declining, terrestrial, insectivorous bird - Catrin F. Eden; Simon Gillings; Richard K. Broughton; Bart Donato; Chris M. Hewson; Stuart P. Sharp (Conservation Biology, 2026)
Insectivorous, Afro‐Palearctic migrant birds provide cross‐border ecosystem services, but many are declining rapidly. The complex life cycle of migrant birds makes their conservation difficult, but understanding where they spend time during the breeding season can help indicate where those actions will be most effective. We used the spotted flycatcher ( Muscicapa striata ), a declining, Afro‐Palearctic, migratory insectivore and habitat generalist, as a model to examine how river density and land‐cover change were associated with loss and colonization during the breeding season of 2 × 2‐km national atlas survey areas from 1990 to 2010. Greater river density was associated with a lower probability of loss (odds ratio [OR] 0.8) between survey periods and a higher probability of colonization (OR 1.25). Loss was associated with increases in urban land cover (OR 1.17), and, unexpectedly, colonization was negatively associated with increases in woodland (OR 0.91) and standing freshwater (OR 0.94). Our results suggest that habitat creation is unlikely to provide sufficient benefits for some insectivorous birds within the time needed for population recovery. Thus, efforts should focus on the protection and improvement of established habitats. River density was strongly associated with the persistence of the spotted flycatcher, and this finding highlights that understanding the benefits of freshwater habitat for terrestrial species should be a priority for conservation management.

Correction: Marine distribution and habitat use by Snow Petrels Pagodroma nivea in East Antarctica throughout the non-breeding period - Benjamin Viola; Barbara Wienecke; Cara-Paige Green; Stuart Corney; Ben Raymond; Colin Southwell; Michael D. Sumner; Patti Virtue; Simon Wotherspoon; Louise Emmerson (Frontiers in Marine Science, 2026)

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

Evolution of Paleogene to Early Miocene deep-water provenance sources in Sabah, northern Borneo reveals changing Proto-South China Sea paleogeography - H. Tim Breitfeld; Marco W.A. van Hattum; Robert Hall; Stuart Burley; Juliane Hennig-Breitfeld; Max Franzel; Simon M. Suggate; Pieter Vermeesch; Max Webb (Tectonophysics, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Acoustic Monitoring Enables Multi‐Taxa Conservation Assessment and Prioritisation Over Large Scales and for Rare and Cryptic Species - Adham Ashton‐Butt; Stuart E. Newson; Jeffrey W. Doser; Simon Gillings; Tatiana Kornienko; Viktar Fenchuk; James W. Pearce‐Higgins; Chris Scott; Philip W. Atkinson (Global Ecology and Biogeography, 2025)
Aim To combat the global biodiversity crisis, robust and scalable data are needed to target, monitor and evaluate conservation efforts, particularly in data‐poor regions and for cryptic taxa. Passive acoustic monitoring (PAM) has the potential to provide solutions, but real‐world examples are still rare. We demonstrate how PAM data can be used to rapidly and effectively map distributions of multiple taxa over large scales, in data‐poor regions. We show how these data can be used to assess the importance of existing protected areas and prioritise future conservation efforts, including for rare and cryptic species often neglected in such assessments. Location Global with a case study from Polesia, Eastern Europe. Time Period Present. Major Taxa Studied Bats, Birds, Small mammals and Bush crickets. Methods Using machine‐learning and manual verification, we identified bats, nocturnally active birds, small mammals and bush crickets from over 34,000 monitoring hours at 506 sites in the Polesia region of Belarus and Ukraine. Using multi‐species generalised mixed models in a Bayesian framework, we then predicted occupancy and acoustic activity for these species and their associations with protected areas, over a 151,000 km 2 project area. We identified areas of high conservation priority as measured by species richness and/or importance for globally or regionally threatened species. Main Conclusions Our approach provides a roadmap for collecting and processing large‐scale, multi‐taxa biodiversity data using passive acoustic monitoring. In our case study region, we show that although existing protected areas contain a relatively large proportion of high conservation priority areas, there are significant gaps in the protected area network. We also show low surrogacy of areas of high conservation priority between taxa at fine scales, but did at larger scales, showing the importance of multi‐taxa monitoring to prioritise protected areas that conserve a wide variety of species.

Reticulospinal and corticospinal responses in long-term strength-trained and untrained adults - Meghan Tanel; Dawson J. Kidgell; Sakari Vekki; Juha P. Ahtiainen; Gonzalo Gomez-Guerrero; Eeli J. Halonen; Stuart N. Baker; Simon Walker (European Journal of Applied Physiology, 2025)
Purpose Studies investigating neural adaptation to strength training have yet to determine the loci of previously observed improvements in motor pathway function. While transcranial magnetic stimulation (TMS) studies have typically focused on the corticospinal tract, recent evidence from primates suggests that the subcortical reticulospinal tract may be the primary candidate for adaptation. Methods: Using a cross-sectional comparison, long-term strength-trained athletes ( n = 15, 11M/4F, 32 ± 6 y) and untrained adults ( n = 18, 11M/7F, 32 ± 4 y) underwent a series of neurophysiological tests designed to target corticospinal and reticulospinal functioning based on biceps brachii muscle responses. The StartReact test was used to determine reaction time, rate of torque development, and muscle activity in response to visual (V), visual–auditory (VA, 80 dB), and visual–startle (VS, 120 dB) cues. Reaction times were used to calculate reticulospinal gain ([V–VS]/[V–VA]). Neuro-navigated monophasic TMS to the motor cortex was given during low-force level isometric voluntary contractions (10% of maximum) with both posterior–anterior (100–180% active motor threshold) and anterior–posterior currents (120% active motor threshold). Motor evoked potentials (MEPs) from stimuli given at 120% active motor threshold were compared to startle cue-conditioned responses and anterior–posterior current responses. Results: Untrained adults benefitted more from StartReact (reticulospinal gain, p = 0.003), whereas strength-trained athletes showed greater MEP size at higher stimulation intensities (180% active motor threshold, p = 0.048, 140–180% area-under-the-curve, p = 0.020) and shorter silent period (180% active motor threshold, p = 0.035). Conclusions: Evidence provided here suggests greater cortico-reticulospinal excitability/functioning in long-term strength-trained athletes.

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Consistent Unimodal Body Length Distributions in Hundreds of Reef Fishes Across Diverse Life Histories - Freddie J. Heather; Shane A. Richards; Nils C. Krueck; Rick D. Stuart‐Smith; Simon J. Brandl; Jordan M. Casey; Graham J. Edgar; Neville Barrett; Valeriano Parravicini; Asta Audzijonyte (Fish and Fisheries, 2025)
Animal body size distributions result from interactions of growth, mortality and recruitment. In ecology and fisheries science, theoretical models of fish body size distributions are widely used but rely on life‐history parameters—growth coefficient (K) and natural mortality rate (M)—that remain unknown for most species and are challenging to estimate. Analysing data from underwater visual surveys and exhaustive sampling, representing 3068 populations across 797 species of shallow‐water, mostly unfished marine fishes, we demonstrate that post‐recruitment body length distributions exhibit a consistent unimodal shape across species and populations. When scaled to the mean body length, these distributions are strikingly similar across all teleost and elasmobranch species, with diverse life histories and maximum body sizes ranging from 1 cm to 3 m. Observed size structure can be approximated by a truncated normal distribution with a coefficient of variation of ~0.34 (SE = 0.002). Such consistent observed body size distributions could be aligned with Beverton–Holt population dynamics theory, if assuming an M/K ratio of ~1.5 and logistic observational selectivity with 50% detectability at ~40% of maximum body length. Alternatively, observed distributions could reflect deviations from theoretical expectations, and reconciling the unimodal distributions with theory may require relaxing some model assumptions, such as continuous recruitment, constant density‐independent growth or constant natural mortality. Overall, the consistency of population‐ and species‐level body length distributions means that unfished size structure could be predicted from a single body size parameter. It also suggests evolutionary convergence of diverse growth and mortality processes towards a narrow range of viable outcomes.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Pets and related allergens modify the association between early life DEHP exposure and respiratory outcomes in children - Luyao Zhang; Ruixue Dai; Wendy Lou; Piush Mandhane; Theo J. Moraes; Elinor Simons; Peter S. Thorne; Teresa To; Stuart E. Turvey; Padmaja Subbarao; Jeffrey R. Brook (Environmental Research, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Unifying Coral Reef States Through Space and Time Reveals a Changing Ecosystem - Simon J. Brandl; Jérémy Carlot; Rick D. Stuart‐Smith; Sally A. Keith; Nicholas A. J. Graham; Graham J. Edgar; Jérémy Wicquart; Shaun K. Wilson; Rucha Karkarey; Mary K. Donovan; Jesus E. Arias‐Gonzalez; Rohan Arthur; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological state shifts that alter the structure and function of entire ecosystems are a concerning consequence of human impact. Yet, when, where and why discrete ecological states emerge remains difficult to predict and monitor, especially in high‐diversity systems. We sought to quantify state shifts and their drivers through space and time in the most ecologically complex marine ecosystem: tropical coral reefs. Location Worldwide. Time Period 1987–2019. Major Taxa Studied Coral reef communities. Methods Using a global dataset of 3375 coral reef surveys, along with 13 time series datasets ranging between 1987 and 2019, we applied a novel double‐dichotomy approach to classify coral reefs into four simplified and discrete states based on the relative contributions of corals versus algae to benthic cover and small‐bodied versus large‐bodied fishes to fish standing stock. We then examined state shifts considering a range of spatial predictors and tested whether states have shifted directionally over time, and the nature of the most common transitions. Results We show that geographic, environmental and anthropogenic context fundamentally shapes coral reef states at the local scale, which explains disparities among case studies, and stakes out critical baseline expectations for regional management efforts. We also reveal clear multi‐decadal state shifts on coral reefs: over time, systems dominated by reef‐building corals and small‐bodied, planktivorous fishes tend to have been replaced with reefs characterised by algae and larger‐bodied fishes. Main Conclusions Our results suggest a previously unrecognised transition from systems that harness external subsidies through small‐bodied consumers associated with structurally complex live corals, to herbivore‐dominated systems with stronger bottom‐up dynamics. Overall, the partitioning of complex reef ecosystems into a small suite of discrete ecological states suggests that spatial context‐dependency, shifting baselines and changes in reef functioning are crucial considerations for coral reef management in the 21st century.

The many ages of Triton: New crater counts on the Voyager high-resolution image sequence and implications for impactor provenance - William B. McKinnon; Kelsi N. Singer; Stuart J. Robbins; Michelle R. Kirchoff; Simon B. Porter; Paul M. Schenk; Ted Stryk; Jeffrey M. Moore (Icarus, 2024)

Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2024) - Peter Simmonds; Evelien M. Adriaenssens; Elliot J. Lefkowitz; Hanna M. Oksanen; Stuart G. Siddell; Francisco Murilo Zerbini; Poliane Alfenas-Zerbini; Frank O. Aylward; Donald M. Dempsey; Bas E. Dutilh; Juliana Freitas-Astúa; María Laura García; et al. (Archives of Virology, 2024)
This article reports changes to virus taxonomy and taxon nomenclature that were approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in April 2024. The entire ICTV membership was invited to vote on 203 taxonomic proposals that had been approved by the ICTV Executive Committee (EC) in July 2023 at the 55th EC meeting in Jena, Germany, or in the second EC vote in November 2023. All proposals were ratified by online vote. Taxonomic additions include one new phylum ( Ambiviricota ), one new class, nine new orders, three new suborders, 51 new families, 18 new subfamilies, 820 new genera, and 3547 new species (excluding taxa that have been abolished). Proposals to complete the process of species name replacement to the binomial (genus + species epithet) format were ratified. Currently, a total of 14,690 virus species have been established.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Lincosamide monotherapy treatment of methicillin-resistant Staphylococcus aureus pneumonia in tropical Australia: a case series - Stuart Campbell; Simon Smith; Josh Hanson (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Existing recommended first-line antibiotic agents for MRSA pneumonia have several shortcomings. We reviewed 29 cases of community- and hospital-acquired MRSA pneumonia managed at our hospital. Lincosamide monotherapy was administered to 21/29 (72%) and was the predominant antibiotic regimen (> 50% course duration) in 19/29 (66%). Patients receiving lincosamide-predominant monotherapy were no more likely to die or require intensive care unit admission than patients receiving vancomycin-predominant monotherapy (5/19 (26%) versus 4/7 (57%), p = 0.19); 5/7 (71%) patients admitted to ICU and 4/5 (80%) bacteraemic patients received lincosamide-predominant monotherapy. MRSA pneumonia can be safely treated with lincosamide monotherapy if the isolate is susceptible.

Can nutritional programming in Atlantic salmon (Salmo salar) be optimised with a reduced stimulus period? - Stuart McMillan; Samuel A.M. Martin; Elżbieta Król; Fernando Norambuena; Simon Baumgärtner; Xu Gong; Marwa Mamdouh Tawfik; Brett Glencross; John F. Taylor; Douglas R. Tocher; Mónica B. Betancor (Aquaculture, 2024)

Predicting recreational water quality and public health safety in urban estuaries using Bayesian Networks - Simon D. Lloyd; Guido Carvajal; Meredith Campey; Nerida Taylor; Paul Osmond; David J. Roser; Stuart J. Khan (Water Research, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Multivalent cations modulating microstructure and interactions of potato protein and fungal hyphae in a functional meat analogue - Mary C. Okeudo-Cogan; Shuyue Yang; Brent S. Murray; Rammile Ettelaie; Simon D. Connell; Stewart Radford; Stuart Micklethwaite; Yoselin Benitez-Alfonso; Richa Yeshvekar; Anwesha Sarkar (Food Hydrocolloids, 2024)

Understanding and addressing shortfalls in European wild bee data - Leon Marshall; Nicolas Leclercq; Luísa G. Carvalheiro; Holger H. Dathe; Bernhard Jacobi; Michael Kuhlmann; Simon G. Potts; Pierre Rasmont; Stuart P.M. Roberts; Nicolas J. Vereecken (Biological Conservation, 2024)

Mean reef fish body size decreases towards warmer waters - Amy Rose Coghlan; Julia L. Blanchard; Simon Wotherspoon; Rick D. Stuart‐Smith; Graham J. Edgar; Neville Barrett; Asta Audzijonyte (Ecology Letters, 2024)
Aquatic ectotherms often attain smaller body sizes at higher temperatures. By analysing ~15,000 coastal‐reef fish surveys across a 15°C spatial sea surface temperature (SST) gradient, we found that the mean length of fish in communities decreased by ~5% for each 1°C temperature increase across space, or 50% decrease in mean length from 14 to 29°C mean annual SST. Community mean body size change was driven by differential temperature responses within trophic groups and temperature‐driven change in their relative abundance. Herbivores, invertivores and planktivores became smaller on average in warmer temperatures, but no trend was found in piscivores. Nearly 25% of the temperature‐related community mean size trend was attributable to trophic composition at the warmest sites, but at colder temperatures, this was

Habitat structure shapes temperate reef assemblages across regional environmental gradients - Tim Jackson-Bué; Ally J. Evans; Peter J. Lawrence; Paul R. Brooks; Sophie L. Ward; Stuart R. Jenkins; Pippa J. Moore; Tasman P. Crowe; Simon P. Neill; Andrew J. Davies (Science of The Total Environment, 2024)

Organophosphate ester flame retardants and plasticizers in house dust and mental health outcomes among Canadian mothers: A nested prospective cohort study in CHILD - Stephanie A. Foster; Molly L. Kile; Perry Hystad; Miriam L. Diamond; Liisa M. Jantunen; Piush J. Mandhane; Theo J. Moraes; Garthika Navaranjan; James A. Scott; Elinor Simons; Padmaja Subbarao; Tim K. Takaro; et al. (Environmental Research, 2024)

The role of mantle melting in granite-associated hydrothermal systems: He–Ar isotopes in fluids responsible for Sn–Ag–Pb–Zn mineralization in northeast China - Zhenhua Zhou; Jingwen Mao; Finlay M. Stuart; Xinkai Chen; Simon A. Wilde; Hegen Ouyang; Xu Gao; Jiaqi Zhao (Mineralium Deposita, 2023)

Marine distribution and habitat use by Snow Petrels Pagodroma nivea in East Antarctica throughout the non-breeding period - Benjamin Viola; Barbara Wienecke; Cara-Paige Green; Stuart Corney; Ben Raymond; Colin Southwell; Michael D. Sumner; Patti Virtue; Simon Wotherspoon; Louise Emmerson (Frontiers in Marine Science, 2023)
The relationships between flying Antarctic seabirds and their at-sea environments remain poorly understood, particularly outside of the breeding season. Improving our knowledge of how these marine predators use their habitat is a critical step towards conservation of these species. We tracked 27 adult Snow Petrels from two large breeding colonies in East Antarctica during the Austral winter (non-breeding period) – when they are primarily at sea away from their nesting sites. During this time, Snow Petrel habitat use was most associated with bathymetry (> 5000 m), low sea-surface height, relatively close distance to the southern boundary of the Antarctic Circumpolar Current, relatively close distance to the ice-edge, relatively high sea-ice concentration, and low sea-surface temperature. Individuals displayed various movement patterns: 20 birds occupied overlapping winter areas that ranged broadly (up to 2000 km) from their breeding sites. The remaining birds ventured far beyond their breeding sites – reaching a maximal distance from the colony of 5,268 km. One individual circumnavigated Antarctica. Daily activity patterns were related to day length, with peak activity occurring near dawn and dusk. Nocturnal activity increased from March until August/September. Key results reveal and depict Snow Petrel habitat maps for the non-breeding period in the East Antarctic region.

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Understanding the microstructure of a functional meat analogue: Demystifying interactions between fungal hyphae and egg white protein - Mary C. Okeudo-Cogan; Brent S. Murray; Rammile Ettelaie; Simon D. Connell; Stewart J. Radford; Stuart Micklethwaite; Anwesha Sarkar (Food Hydrocolloids, 2023)

European bee diversity: Taxonomic and phylogenetic patterns - Nicolas Leclercq; Leon Marshall; Geoffrey Caruso; Kerry Schiel; Timothy Weekers; Luísa G. Carvalheiro; Holger H. Dathe; Michael Kuhlmann; Denis Michez; Simon G. Potts; Pierre Rasmont; Stuart P. M. Roberts; et al. (Journal of Biogeography, 2023)
Aim Wild bees still face striking shortfalls in knowledge of biodiversity in key regions of the world. This includes Europe, where despite a long tradition of data gathering, the continental scale distribution patterns of wild bees have not been systematically analysed to date. This study aims to characterise large‐scale biodiversity patterns to: (i) understand spatial–temporal heterogeneity in large‐scale databases, (ii) locate genuine diversity hotspots and their relationship with biogeographical patterns or habitats of interests and (iii) identify understudied species and areas to further design conservation actions for most at risk species in key regions. Location Europe. Taxon Bees. Methods We present a continental and standardised study of bee taxonomic and phylogenetic diversity patterns in Europe, using a large compilation of occurrence records of nearly three million validated occurrence records for 1515 wild bee species. Results Southern and eastern Europe suffer from the largest gaps in data availability while northern and western regions benefit from better historical coverage. Our models show that higher wild bee diversity in Europe is hosted in xeric, warm areas, as highlighted by a clear latitudinal gradient. However, phylogenetic diversity is predicted to be more homogenous across Europe than taxonomic diversity, suggesting that policies and strategies targeted to protect species richness may differ from those targeting greater phylogenetic diversity. Main conclusions This study represents a significant advance in the characterisation of wild bee distribution patterns across Europe and is an important stepping stone towards the design of more targeted survey efforts and conservation actions of this key group of pollinators. This, in turn, will provide the data necessary to improve the spatiotemporal coverage in a context of ongoing and future Europe‐wide monitoring schemes, to ultimately develop cost‐effective, coordinated and evidence‐based conservation actions and tailored habitat management actions that can be implemented on a smaller scale.

GLOF hazard, exposure, vulnerability, and risk assessment of potentially dangerous glacial lakes in the Bhutan Himalaya - Sonam Rinzin; Guoqing Zhang; Ashim Sattar; Sonam Wangchuk; Simon K. Allen; Stuart Dunning; Menger Peng (Journal of Hydrology, 2023)

Toward a forest biomass reference measurement system for remote sensing applications - Nicolas Labrière; Stuart J. Davies; Mathias I. Disney; Laura I. Duncanson; Martin Herold; Simon L. Lewis; Oliver L. Phillips; Shaun Quegan; Sassan S. Saatchi; Dmitry G. Schepaschenko; Klaus Scipal; Plinio Sist; et al. (Global Change Biology, 2023)
Forests contribute to climate change mitigation through carbon storage and uptake, but the extent to which this carbon pool varies in space and time is still poorly known. Several Earth Observation missions have been specifically designed to address this issue, for example, NASA's GEDI, NASA‐ISRO's NISAR and ESA's BIOMASS. Yet, all these missions' products require independent and consistent validation. A permanent, global, in situ, site‐based forest biomass reference measurement system relying on ground data of the highest possible quality is therefore needed. Here, we have assembled a list of almost 200 high‐quality sites through an in‐depth review of the literature and expert knowledge. In this study, we explore how representative these sites are in terms of their coverage of environmental conditions, geographical space and biomass‐related forest structure, compared to those experienced by forests worldwide. This work also aims at identifying which sites are the most representative, and where to invest to improve the representativeness of the proposed system. We show that the environmental coverage of the system does not seem to improve after at least the 175 most representative sites are included, but geographical and structural coverages continue to improve as more sites are added. We highlight the areas of poor environmental, geographical, or structural coverage, including, but not limited to, Canada, the western half of the USA, Mexico, Patagonia, Angola, Zambia, eastern Russia, and tropical and subtropical highlands (e.g. in Colombia, the Himalayas, Borneo, Papua). For the proposed system to succeed, we stress that (1) data must be collected and processed applying the same standards across all countries and continents; (2) system establishment and management must be inclusive and equitable, with careful consideration of working conditions; and (3) training and site partner involvement in downstream activities should be mandatory.

Funding evidence‐based conservation - Danni Parks; Nida Al‐Fulaij; Clare Brook; Stuart H. M. Butchart; Jean‐Gaël Collomb; David Cope; Simon Dowell; Becky Falkingham; Winifred F. Frick; Douglas Gibbs; Emily E. Gray; Nicolas Heard; et al. (Conservation Biology, 2022)

Earth stewardship: Shaping a sustainable future through interacting policy and norm shifts - F. Stuart Chapin; Elke U. Weber; Elena M. Bennett; Reinette Biggs; Jeroen van den Bergh; W. Neil Adger; Anne-Sophie Crépin; Stephen Polasky; Carl Folke; Marten Scheffer; Kathleen Segerson; John M. Anderies; et al. (Ambio, 2022)
Transformation toward a sustainable future requires an earth stewardship approach to shift society from its current goal of increasing material wealth to a vision of sustaining built, natural, human, and social capital—equitably distributed across society, within and among nations. Widespread concern about earth’s current trajectory and support for actions that would foster more sustainable pathways suggests potential social tipping points in public demand for an earth stewardship vision. Here, we draw on empirical studies and theory to show that movement toward a stewardship vision can be facilitated by changes in either policy incentives or social norms. Our novel contribution is to point out that both norms and incentives must change and can do so interactively. This can be facilitated through leverage points and complementarities across policy areas, based on values, system design, and agency. Potential catalysts include novel democratic institutions and engagement of non-governmental actors, such as businesses, civic leaders, and social movements as agents for redistribution of power. Because no single intervention will transform the world, a key challenge is to align actions to be synergistic, persistent, and scalable.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Street-level green spaces support a key urban population of the threatened Hispaniolan parakeet Psittacara chloropterus - Matthew Geary; Celia J. Brailsford; Laura I. Hough; Fraser Baker; Simon Guerrero; Yolanda M. Leon; Nigel J. Collar; Stuart J. Marsden (Urban Ecosystems, 2021)
While urbanisation remains a major threat to biodiversity, urban areas can sometimes play an important role in protecting threatened species, especially exploited taxa such as parrots. The Hispaniolan Parakeet Psittacara chloropterus has been extirpated across much of Hispaniola, including from most protected areas, yet Santo Domingo (capital city of the Dominican Republic) has recently been found to support the island’s densest remaining population. In 2019, we used repeated transects and point-counts across 60 1 km 2 squares of Santo Domingo to examine the distribution of parakeets, identify factors that might drive local presence and abundance, and investigate breeding ecology. Occupancy models indicate that parakeet presence was positively related to tree species richness across the city. N-Mixture models show parakeet encounter rates were correlated positively with species richness of trees and number of discrete ‘green’ patches (> 100 m 2 ) within the survey squares. Hispaniolan Woodpecker Melanerpes striatus , the main tree-cavity-producing species on Hispaniola, occurs throughout the city, but few parakeet nests are known to involve the secondary use of its or other cavities in trees/palms. Most parakeet breeding (perhaps 50–100 pairs) appears to occur at two colonies in old buildings, and possibly only a small proportion of the city’s 1500+ parakeets that occupy a single roost in street trees breed in any year. Our models emphasise the importance of parks and gardens in providing feeding resources for this IUCN Vulnerable species. Hispaniola’s urban centres may be strongholds for populations of parakeets and may even represent sources for birds to recolonise formerly occupied areas on the island.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Role of air–sea fluxes and ocean surface density in the production of deep waters in the eastern subpolar gyre of the North Atlantic - Tillys Petit; M. Susan Lozier; Simon A. Josey; Stuart A. Cunningham (Ocean Science, 2021)
Wintertime convection in the North Atlantic Ocean is a key component of the global climate as it produces dense waters at high latitudes that flow equatorward as part of the Atlantic Meridional Overturning Circulation (AMOC). Recent work has highlighted the dominant role of the Irminger and Iceland basins in the production of North Atlantic Deep Water. Dense water formation in these basins is mainly explained by buoyancy forcing that transforms surface waters to the deep waters of the AMOC lower limb. Air–sea fluxes and the ocean surface density field are both key determinants of the buoyancy-driven transformation. We analyze these contributions to the transformation in order to better understand the connection between atmospheric forcing and the densification of surface water. More precisely, we study the impact of air–sea fluxes and the ocean surface density field on the transformation of subpolar mode water (SPMW) in the Iceland Basin, a water mass that “pre-conditions” dense water formation downstream. Analyses using 40 years of observations (1980–2019) reveal that the variance in SPMW transformation is mainly influenced by the variance in density at the ocean surface. This surface density is set by a combination of advection, wind-driven upwelling and surface fluxes. Our study shows that the latter explains ∼ 30 % of the variance in outcrop area as expressed by the surface area between the outcropped SPMW isopycnals. The key role of the surface density in SPMW transformation partly explains the unusually large SPMW transformation in winter 2014–2015 over the Iceland Basin.

Compound-Specific Stable Isotope Analysis of Amino Acids in Pelagic Shark Vertebrae Reveals Baseline, Trophic, and Physiological Effects on Bulk Protein Isotope Records - Sarah Magozzi; Simon R. Thorrold; Leah Houghton; Victoria A. Bendall; Stuart Hetherington; Gonzalo Mucientes; Lisa J. Natanson; Nuno Queiroz; Miguel N. Santos; Clive N. Trueman (Frontiers in Marine Science, 2021)
Variations in stable carbon and nitrogen isotope compositions in incremental tissues of pelagic sharks can be used to infer aspects of their spatial and trophic ecology across life-histories. Interpretations from bulk tissue isotopic compositions are complicated, however, because multiple processes influence these values, including variations in primary producer isotope ratios and consumer diets and physiological processing of metabolites. Here we challenge inferences about shark tropho-spatial ecology drawn from bulk tissue isotope data using data for amino acids. Stable isotope compositions of individual amino acids can partition the isotopic variance in bulk tissue into components associated with primary production on the one hand, and diet and physiology on the other. The carbon framework of essential amino acids (EAAs) can be synthesised de novo only by plants, fungi and bacteria and must be acquired by consumers through the diet. Consequently, the carbon isotopic composition of EAAs in consumers reflects that of primary producers in the location of feeding, whereas that of non-essential amino acids (non-EAAs) is additionally influenced by trophic fractionation and isotope dynamics of metabolic processing. We determined isotope chronologies from vertebrae of individual blue sharks and porbeagles from the North Atlantic. We measured carbon and nitrogen isotope compositions in bulk collagen and carbon isotope compositions of amino acids. Despite variability among individuals, common ontogenetic patterns in bulk isotope compositions were seen in both species. However, while life-history movement inferences from bulk analyses for blue sharks were supported by carbon isotope data from essential amino acids, inferences for porbeagles were not, implying that the observed trends in bulk protein isotope compositions in porbeagles have a trophic or physiological explanation, or are suprious effects. We explored variations in carbon isotope compositions of non-essential amino acids, searching for systematic variations that might imply ontogenetic changes in physiological processing, but patterns were highly variable and did not explain variance in bulk protein δ 13 C values. Isotopic effects associated with metabolite processing may overwhelm spatial influences that are weak or inconsistently developed in bulk tissue isotope values, but interpreting mechanisms underpinning isotopic variation in patterns in non-essential amino acids remains challenging.

Our future in the Anthropocene biosphere - Carl Folke; Stephen Polasky; Johan Rockström; Victor Galaz; Frances Westley; Michèle Lamont; Marten Scheffer; Henrik Österblom; Stephen R. Carpenter; F. Stuart Chapin; Karen C. Seto; Elke U. Weber; et al. (Ambio, 2021)
The COVID-19 pandemic has exposed an interconnected and tightly coupled globalized world in rapid change. This article sets the scientific stage for understanding and responding to such change for global sustainability and resilient societies. We provide a systemic overview of the current situation where people and nature are dynamically intertwined and embedded in the biosphere, placing shocks and extreme events as part of this dynamic; humanity has become the major force in shaping the future of the Earth system as a whole; and the scale and pace of the human dimension have caused climate change, rapid loss of biodiversity, growing inequalities, and loss of resilience to deal with uncertainty and surprise. Taken together, human actions are challenging the biosphere foundation for a prosperous development of civilizations. The Anthropocene reality—of rising system-wide turbulence—calls for transformative change towards sustainable futures. Emerging technologies, social innovations, broader shifts in cultural repertoires, as well as a diverse portfolio of active stewardship of human actions in support of a resilient biosphere are highlighted as essential parts of such transformations.

Evolution of the African slippery frogs (Anura: Conraua ), including the world’s largest living frog - David C. Blackburn; Stuart V. Nielsen; Michael F. Barej; Joseph Doumbia; Mareike Hirschfeld; N’Goran G. Kouamé; Dwight Lawson; Simon Loader; Caleb Ofori‐Boateng; Edward L. Stanley; Mark‐Oliver Rödel (Zoologica Scripta, 2020)
Although Conraua goliath is well known as the largest living frog species, the diversity and evolution of the genus Conraua across sub‐Saharan Africa remain poorly understood. We present multilocus phylogenetic analyses of the six currently recognized species that provide insights into divergence times, biogeography, body size evolution and undescribed species. An analysis of divergence times demonstrates that crown‐group Conraua arose some time during the latest Oligocene to mid‐Miocene followed by divergence into major lineages in the mid‐Miocene that may reflect the fragmentation of widespread tropical forests in Africa that began at this time. We find three pairs of sister species, C. crassipes + C. beccarii , C. alleni + C. derooi and C. goliath + C. robusta , each of which diverged during the Miocene. These relationships reject phylogenetic hypotheses based solely on biogeography as the geographically peripheral C. beccarii from north‐eastern Africa is nested within western African species and the Central African species do not form a clade. Our species delimitation analyses provide support for undescribed species in C. alleni , C. beccarii and C. derooi , and possibly C. crassipes , suggesting that the current taxonomy substantially underestimates species diversity. There is no clear directional trend of either increasing or decreasing body size in Conraua and the three largest species do not form a clade. With a robust phylogenetic hypothesis in hand, further field‐based studies are needed to understand the evolution of morphology and life history in this charismatic African anuran clade.

Thioredoxin System Protein Expression Is Associated with Poor Clinical Outcome in Adult and Paediatric Gliomas and Medulloblastomas - Anqi Yao; Sarah J. Storr; Khaled Al-hadyan; Ruman Rahman; Stuart Smith; Richard Grundy; Simon Paine; Stewart G. Martin (Molecular Neurobiology, 2020)
The thioredoxin (Trx) system is an important enzyme family that regulates cellular redox homeostasis. Protein expression of Trx system family members has been assessed in various cancers and linked to various clinicopathological variables, disease progression, treatment response and survival outcomes but information is lacking in brain tumours. Expression of the system was therefore examined, by immunohistochemistry in different brain tumour types, adult and paediatric cases, to determine if expression was of importance to clinical outcome. Trx system proteins were expressed, to variable levels, across all brain tumour types with significant variations in expression between different tumour types/grades/regions. High Trx reductase (TrxR) expression was linked to worse prognosis across all cohorts. High cytoplasmic TrxR expression was significantly associated with adverse overall survival (OS) in adult glioblastoma ( P = 0.027) and paediatric low-grade glioma (LGG) patients ( P = 0.012). High expression of nuclear TrxR, cytoplasmic and nuclear Trx and Trx-interacting protein (TxNIP) was associated with improved OS in paediatric LGGs ( P = 0.031, P < 0.001, P = 0.044 and P = 0.018, respectively). For patients with high-grade gliomas, both high cytoplasmic TrxR and Trx expression were associated with poor OS ( P = 0.002 and P = 0.007, respectively). In medulloblastoma, high expression of cytoplasmic TrxR and Trx and nuclear Trx was associated with worse prognosis ( P = 0.013, P = 0.033 and P = 0.007, respectively); with cytoplasmic TrxR and nuclear Trx remaining so in multivariate analysis ( P = 0.009 and P = 0.013, respectively). The consistent finding that high levels of cytoplasmic TrxR are associated with a worse prognosis across all cohorts suggests that TrxR is an important therapeutic target in brain cancers.

A framework for evaluating the impact of the IUCN Red List of threatened species - Jessica Betts; Richard P. Young; Craig Hilton‐Taylor; Michael Hoffmann; Jon Paul Rodríguez; Simon N. Stuart; E.J. Milner‐Gulland (Conservation Biology, 2020)
The International Union for Conservation of Nature (IUCN) Red List of Threatened Species, a species extinction risk assessment tool, has been guiding conservation efforts for over 5 decades. It is widely assumed to have been instrumental in preventing species from moving closer to extinction and driving recoveries. However, the impact of the IUCN Red List in guiding conservation has not been evaluated. We conducted, transcribed, and coded interviews with experts who use the IUCN Red List across a range of sectors to understand how the list is used in conservation. We developed a theory of change to illustrate how and why change is expected to occur along causal pathways contributing to the long‐term goal of the IUCN Red List and an evaluation framework with indicators for measuring the impact of the IUCN Red List in generating scientific knowledge, raising awareness among stakeholders, designating priority conservation sites, allocating funding and resources, influencing development of legislation and policy, and guiding targeted conservation action (key themes). Red‐list assessments were the primary input leading to outputs (scientific knowledge, raised awareness), outcomes (better informed priority setting, access to funding and resource availability, improved legislation and policy), and impact (implemented conservation action leading to positive change) that have resulted in achievement of IUCN Red List goals. To explore feasibility of attributing the difference made by the IUCN Red List across themes, we studied increased scientific knowledge, raised awareness, access to funding and resource allocation, and increased conservation activity. The feasibility exploration showed increased scientific knowledge over time identified through positive trends in publications referring to the IUCN Red List in the literature; raised awareness of the list following high IUCN activity identified by peaks in online search activity; an increased proportion of conservation funding bodies requesting IUCN Red List status in the application process; and, based on interviews with Amphibian Specialist Group members, red‐list assessments were essential in connecting relevant stakeholders and ensuring conservation action. Although we identified the IUCN Red List as a vital tool in global conservation efforts, it was challenging to measure specific impacts because of its ubiquitous nature. We are the first to identify the influence of the IUCN Red List on conservation.

A first look at oxygen isotope records from modern and Holocene‐aged gastropod ( Stenomelania ) shells from Lake Kutubu, Papua New Guinea - Kelsie Long; Larissa Schneider; Ian S. Williams; Stewart J. Fallon; Hilary Stuart‐Williams; Simon Haberle (Journal of Quaternary Science, 2020)
The oxygen isotopic composition of Stenomelania gastropod shells was investigated to reconstruct Holocene palaeoclimate change at Lake Kutubu in the southern highlands of Papua New Guinea. Oxygen isotope (δ 18 O) values recorded in aquatic gastropod shells change according to ambient water δ 18 O values and temperature. The gastropod shells appear to form in oxygen isotopic equilibrium with the surrounding water and record a shift in average shell oxygen isotopic composition through time, probably as a result of warmer/wetter conditions at ca. 600–900 and 5900–6200 cal a bp. Shorter term fluctuations in oxygen isotope values were also identified and may relate to changes in the intensity or source of rainfall. Further δ 18 O analyses of gastropod shells or other carbonate proxies found in the Lake Kutubu sediments are warranted. © 2020 John Wiley & Sons, Ltd.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Ground Data are Essential for Biomass Remote Sensing Missions - Jérôme Chave; Stuart J. Davies; Oliver L. Phillips; Simon L. Lewis; Plinio Sist; Dmitry Schepaschenko; John Armston; Tim R. Baker; David Coomes; Mathias Disney; Laura Duncanson; Bruno Hérault; et al. (Surveys in Geophysics, 2019)

Quantifying species recovery and conservation success to develop an IUCN Green List of Species - H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Molly K. Grace; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; David A. Keith; Barney Long; David P. Mallon; Erik Meijaard; et al. (Conservation Biology, 2018)
Stopping declines in biodiversity is critically important, but it is only a first step toward achieving more ambitious conservation goals. The absence of an objective and practical definition of species recovery that is applicable across taxonomic groups leads to inconsistent targets in recovery plans and frustrates reporting and maximization of conservation impact. We devised a framework for comprehensively assessing species recovery and conservation success. We propose a definition of a fully recovered species that emphasizes viability, ecological functionality, and representation; and use counterfactual approaches to quantify degree of recovery. This allowed us to calculate a set of 4 conservation metrics that demonstrate impacts of conservation efforts to date (conservation legacy); identify dependence of a species on conservation actions (conservation dependence); quantify expected gains resulting from conservation action in the medium term (conservation gain); and specify requirements to achieve maximum plausible recovery over the long term (recovery potential). These metrics can incentivize the establishment and achievement of ambitious conservation targets. We illustrate their use by applying the framework to a vertebrate, an invertebrate, and a woody and an herbaceous plant. Our approach is a preliminary framework for an International Union for Conservation of Nature (IUCN) Green List of Species, which was mandated by a resolution of IUCN members in 2012. Although there are several challenges in applying our proposed framework to a wide range of species, we believe its further development, implementation, and integration with the IUCN Red List of Threatened Species will help catalyze a positive and ambitious vision for conservation that will drive sustained conservation action.

Palaeotoxicity: reconstructing the risk of multiple sedimentary pollutants to freshwater organisms - Neil L. Rose; Simon D. Turner; Handong Yang; Congqiao Yang; Charlotte Hall; Stuart Harrad (Environmental Geochemistry and Health, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Safety, tolerability and pharmacokinetics of GSK3008348, a novel integrin αvβ6 inhibitor, in healthy participants - Charlotte H. Maden; David Fairman; Michelle Chalker; Maria J. Costa; William A. Fahy; Nadia Garman; Pauline T. Lukey; Tim Mant; Simon Parry; Juliet K. Simpson; Robert J. Slack; Stuart Kendrick; et al. (European Journal of Clinical Pharmacology, 2018)

A cross‐continental comparison of assemblages of seed‐ and fruit‐feeding insects in tropical rain forests: Faunal composition and rates of attack - Yves Basset; Chris Dahl; Richard Ctvrtecka; Sofia Gripenberg; Owen T. Lewis; Simon T. Segar; Petr Klimes; Héctor Barrios; John W. Brown; Sarayudh Bunyavejchewin; Buntika A. Butcher; Anthony I. Cognato; et al. (Journal of Biogeography, 2018)
Aim Insects feeding on seeds and fruits represent interesting study systems, potentially able to lower the fitness of their host plants. In addition to true seed eaters, a suite of insects feed on the fleshy parts of fruits. We examined the likelihood of community convergence in whole insect assemblages attacking seeds/fruits in three tropical rain forests. Location Three Forest GEO permanent forest plots within different biogeographical regions: Barro Colorado Island (Panama), Khao Chong (Thailand) and Wanang (Papua New Guinea). Methods We surveyed 1,186 plant species and reared 1.1 ton of seeds/fruits that yielded 80,600 insects representing at least 1,678 species. We assigned seeds/fruits to predation syndromes on the basis of plant traits relevant to insects, seed/fruit appearance and mesocarp thickness. Results We observed large differences in insect faunal composition, species richness and guild structure between our three study sites. We hypothesize that the high species richness of insect feeding on seeds/fruits in Panama may result from a conjunction of low plant species richness and high availability of dry fruits. Insect assemblages were weakly influenced by seed predation syndromes, both at the local and regional scale, and the effect of host phylogeny varied also among sites. At the driest site (Panama), the probability of seeds of a plant species being attacked depended more on seed availability than on the measured seed traits of that plant species. However, when seeds were attacked, plant traits shaping insect assemblages were difficult to identify and not related to seed availability. Main conclusions We observed only weak evidence of community convergence at the intercontinental scale among these assemblages. Our study suggests that seed eaters may be most commonly associated with dry fruits at relatively dry tropical sites where fleshy fruits may be less prevalent.

Clarifying the key biodiversity areas partnership and programme - Simon N. Stuart; Thomas M. Brooks; Stuart H. M. Butchart; Wendy Elliott; Melanie Heath; Dieter Hoffmann; Leslie Honey; Irina Kostadinova; Penny Langhammer; Olivier Langrand; Susan Lieberman; Daniel Marnewick; et al. (Biodiversity and Conservation, 2018)

Brain cortical characteristics of lifetime cognitive ageing - Simon R. Cox; Mark E. Bastin; Stuart J. Ritchie; David Alexander Dickie; Dave C. Liewald; Susana Muñoz Maniega; Paul Redmond; Natalie A. Royle; Alison Pattie; Maria Valdés Hernández; Janie Corley; Benjamin S. Aribisala; et al. (Brain Structure and Function, 2018)

Risk and protective factors for structural brain ageing in the eighth decade of life - Stuart J. Ritchie; Elliot M. Tucker-Drob; Simon R. Cox; David Alexander Dickie; Maria del C. Valdés Hernández; Janie Corley; Natalie A. Royle; Paul Redmond; Susana Muñoz Maniega; Alison Pattie; Benjamin S. Aribisala; Adele M. Taylor; et al. (Brain Structure and Function, 2017)

Climate adaptation of food value chains: the implications of varying consumer acceptance - Lilly Lim-Camacho; Anoma Ariyawardana; Gemma K. Lewis; Steven J. Crimp; Simon Somogyi; Brad Ridoutt; Stuart Mark Howden (Regional Environmental Change, 2017)

Stable isotopes and mtDNA reveal niche segregation but no evidence of intergradation along a habitat gradient in the Lesser Whitethroat complex (Sylvia curruca; Passeriformes; Aves) - Stephen C. Votier; Simon Aspinall; Stuart Bearhop; David Bilton; Jason Newton; Per Alström; Paul Leader; Geoff Carey; Robert W. Furnes; Urban Olsson (Journal of Ornithology, 2016)

Mass‐flowering crops dilute pollinator abundance in agricultural landscapes across Europe - Andrea Holzschuh; Matteo Dainese; Juan P. González‐Varo; Sonja Mudri‐Stojnić; Verena Riedinger; Maj Rundlöf; Jeroen Scheper; Jennifer B. Wickens; Victoria J. Wickens; Riccardo Bommarco; David Kleijn; Simon G. Potts; et al. (Ecology Letters, 2016)
Mass‐flowering crops ( MFC s) are increasingly cultivated and might influence pollinator communities in MFC fields and nearby semi‐natural habitats ( SNH s). Across six European regions and 2 years, we assessed how landscape‐scale cover of MFC s affected pollinator densities in 408 MFC fields and adjacent SNH s. In MFC fields, densities of bumblebees, solitary bees, managed honeybees and hoverflies were negatively related to the cover of MFC s in the landscape. In SNH s, densities of bumblebees declined with increasing cover of MFC s but densities of honeybees increased. The densities of all pollinators were generally unrelated to the cover of SNH s in the landscape. Although MFC fields apparently attracted pollinators from SNH s, in landscapes with large areas of MFC s they became diluted. The resulting lower densities might negatively affect yields of pollinator‐dependent crops and the reproductive success of wild plants. An expansion of MFC s needs to be accompanied by pollinator‐supporting practices in agricultural landscapes.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Brain white matter structure and information processing speed in healthy older age - Ksenia A. Kuznetsova; Susana Muñoz Maniega; Stuart J. Ritchie; Simon R. Cox; Amos J. Storkey; John M. Starr; Joanna M. Wardlaw; Ian J. Deary; Mark E. Bastin (Brain Structure and Function, 2016)

Glycoproteomic studies of IgE from a novel hyper IgE syndrome linked to PGM3 mutation - Gang Wu; Paul G. Hitchen; Maria Panico; Simon J. North; Mohamed-Ridha Barbouche; Daniel Binet; Howard R. Morris; Anne Dell; Stuart M. Haslam (Glycoconjugate Journal, 2016)

A framework for understanding climate change impacts on coral reef social–ecological systems - Joshua Eli Cinner; Morgan Stuart Pratchett; Nicholas Anthony James Graham; Vanessa Messmer; Mariana Menezes Prata Bezerra Fuentes; Tracy Ainsworth; Natalie Ban; Line Kolind Bay; Jessica Blythe; Delphine Dissard; Simon Dunn; Louisa Evans; et al. (Regional Environmental Change, 2016)

Quantifying the relative irreplaceability of important bird and biodiversity areas - Moreno Di Marco; Thomas Brooks; Annabelle Cuttelod; Lincoln D.C. Fishpool; Carlo Rondinini; Robert J. Smith; Leon Bennun; Stuart H.M. Butchart; Simon Ferrier; Ruud P.B. Foppen; Lucas Joppa; Diego Juffe‐Bignoli; et al. (Conservation Biology, 2016)
World governments have committed to increase the global protected areas coverage by 2020, but the effectiveness of this commitment for protecting biodiversity depends on where new protected areas are located. Threshold‐ and complementarity‐based approaches have been independently used to identify important sites for biodiversity. We brought together these approaches by performing a complementarity‐based analysis of irreplaceability in important bird and biodiversity areas (IBAs), which are sites identified using a threshold‐based approach. We determined whether irreplaceability values are higher inside than outside IBAs and whether any observed difference depends on known characteristics of the IBAs. We focused on 3 regions with comprehensive IBA inventories and bird distribution atlases: Australia, southern Africa, and Europe. Irreplaceability values were significantly higher inside than outside IBAs, although differences were much smaller in Europe than elsewhere. Higher irreplaceability values in IBAs were associated with the presence and number of restricted‐range species; number of criteria under which the site was identified; and mean geographic range size of the species for which the site was identified (trigger species). In addition, IBAs were characterized by higher irreplaceability values when using proportional species representation targets, rather than fixed targets. There were broadly comparable results when measuring irreplaceability for trigger species and when considering all bird species, which indicates a good surrogacy effect of the former. Recently, the International Union for Conservation of Nature has convened a consultation to consolidate global standards for the identification of key biodiversity areas (KBAs), building from existing approaches such as IBAs. Our results informed this consultation, and in particular a proposed irreplaceability criterion that will allow the new KBA standard to draw on the strengths of both threshold‐ and complementarity‐based approaches.

Tectonic subsidence provides insight into possible coral reef futures under rapid sea-level rise - Megan I. Saunders; Simon Albert; Chris M. Roelfsema; Javier X. Leon; Colin D. Woodroffe; Stuart R. Phinn; Peter J. Mumby (Coral Reefs, 2016)

Resource availability affects individual niche variation and its consequences in group-living European badgers Meles meles - Andrew Robertson; Robbie A. McDonald; Richard J. Delahay; Simon D. Kelly; Stuart Bearhop (Oecologia, 2015)

Urbanization changes the composition and bioavailability of dissolved organic matter in headwater streams - Thomas B. Parr; Christopher S. Cronan; Tsutomu Ohno; Stuart E. G. Findlay; Sean M. C. Smith; Kevin S. Simon (Limnology and Oceanography, 2015)
Population growth in cities has resulted in the rapid expansion of urbanized land. Most research and management of stream ecosystems affected by urban expansion has focused on the maintenance and restoration of biotic communities rather than their basal resources. We examined the potential for urbanization to induce bottom‐up ecosystem effects by looking at its influence on dissolved organic matter (DOM) composition and bioavailability and microbial enzyme activity. We selected 113 headwater streams across a gradient of urbanization in central and southern Maine and used elemental and optical analyses, including parallel factor analysis of excitation‐emission matrices, to characterize DOM composition. Results show that fluorescent and stoichiometric DOM composition changed significantly across the rural to urban gradient. Specifically, the proportion of humic‐like allochthonous DOM decreased while that of more bioavailable autochthonous DOM increased in the more urbanized streams. In laboratory incubations, increased autochthonous DOM was associated with a doubling in the decay rate of dissolved organic carbon as well as increased activity of C‐acquiring enzymes. These results suggest that urbanization replaces upstream humic material with more local sources of DOM that turnover more rapidly and may drive bottom‐up changes in microbial communities and affect the quality and quantity of downstream DOM delivery.

Individual foraging specialisation in a social mammal: the European badger (Meles meles) - Andrew Robertson; Robbie A. McDonald; Richard J. Delahay; Simon D. Kelly; Stuart Bearhop (Oecologia, 2014)

Cassava Ivorian bacilliform virus is a member of the genus Anulavirus - Simon W. Scott; Stuart A. MacFarlane; Wendy J. McGavin; Denis Fargette (Archives of Virology, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Density of insect‐pollinated grassland plants decreases with increasing surrounding land‐use intensity - Yann Clough; Johan Ekroos; András Báldi; Péter Batáry; Riccardo Bommarco; Nicolas Gross; Andrea Holzschuh; Sebastian Hopfenmüller; Eva Knop; Mikko Kuussaari; Regina Lindborg; Lorenzo Marini; et al. (Ecology Letters, 2014)
Pollinator declines have raised concerns about the persistence of plant species that depend on insect pollination, in particular by bees, for their reproduction. The impact of pollinator declines remains unknown for species‐rich plant communities found in temperate seminatural grasslands. We investigated effects of land‐use intensity in the surrounding landscape on the distribution of plant traits related to insect pollination in 239 European seminatural grasslands. Increasing arable land use in the surrounding landscape consistently reduced the density of plants depending on bee and insect pollination. Similarly, the relative abundance of bee‐pollination‐dependent plants increased with higher proportions of non‐arable agricultural land (e.g. permanent grassland). This was paralleled by an overall increase in bee abundance and diversity. By isolating the impact of the surrounding landscape from effects of local habitat quality, we show for the first time that grassland plants dependent on insect pollination are particularly susceptible to increasing land‐use intensity in the landscape.

Oligoamides of 2-amino-5-alkylthiazole 4-carboxylic acids: anti-trypanosomal compounds - Stuart Lang; Abedawn I. Khalaf; David Breen; Judith K. Huggan; Carol J. Clements; Simon P. MacKay; Colin J. Suckling (Medicinal Chemistry Research, 2014)

Mapping coral reefs at reef to reef-system scales, 10s–1000s km 2 , using object-based image analysis - Chris Roelfsema; Stuart Phinn; Stacy Jupiter; James Comley; Simon Albert (International Journal of Remote Sensing, 2013)

Species richness declines and biotic homogenisation have slowed down for NW ‐European pollinators and plants - Luísa Gigante Carvalheiro; William E. Kunin; Petr Keil; Jesus Aguirre‐Gutiérrez; Willem Nicolaas Ellis; Richard Fox; Quentin Groom; Stephan Hennekens; Wouter Van Landuyt; Dirk Maes; Frank Van de Meutter; Denis Michez; et al. (Ecology Letters, 2013)
Concern about biodiversity loss has led to increased public investment in conservation. Whereas there is a widespread perception that such initiatives have been unsuccessful, there are few quantitative tests of this perception. Here, we evaluate whether rates of biodiversity change have altered in recent decades in three European countries (Great Britain, Netherlands and Belgium) for plants and flower visiting insects. We compared four 20‐year periods, comparing periods of rapid land‐use intensification and natural habitat loss (1930–1990) with a period of increased conservation investment (post‐1990). We found that extensive species richness loss and biotic homogenisation occurred before 1990, whereas these negative trends became substantially less accentuated during recent decades, being partially reversed for certain taxa (e.g. bees in Great Britain and Netherlands). These results highlight the potential to maintain or even restore current species assemblages (which despite past extinctions are still of great conservation value), at least in regions where large‐scale land‐use intensification and natural habitat loss has ceased.

Whisker growth in wild Eurasian badgers Meles meles: implications for stable isotope and bait marking studies - Andrew Robertson; Robbie A. McDonald; Richard J. Delahay; Simon D. Kelly; Stuart Bearhop (European Journal of Wildlife Research, 2013)

Physical and biological controls on larval dispersal and connectivity in a highly energetic shelf sea - Peter E. Robins; Simon P. Neill; Luis Giménez; Stuart R. Jenkins; Shelagh K. Malham (Limnology and Oceanography, 2013)
Connectivity within marine species plays a fundamental role in population dynamics, genetic diversity, spread of disease, and resilience to human exploitation. However, for shellfish species that are sessile as adults, the larval‐dispersal stage remains largely unresolved. Appreciation of larval connectivity is therefore crucial to population genetics and marine management. We describe a coupled three‐dimensional hydrodynamic and Lagrangian particle tracking model used to simulate larval transport and show how temporal and spatial hydrodynamic changes, together with larval behavior, are likely to affect dispersal. A case study of Irish Sea (United Kingdom) shellfish populations incorporates a wide range of hydrodynamic environments that are prevalent in other marine systems around the world. Our simulations tested two main processes that control larval dispersal: hydrodynamics and vertical migration. Simulated larval cohorts were released from estuaries and soft sediment locations in regions that were oceanographically distinct. Larvae originating from exposed areas could migrate offshore (low retention and high connectivity) and disperse farther than larvae that remained in flood‐dominant estuaries, which promote retention. Simulated self‐recruitment and connectivity with neighboring populations (∼ 50 km apart) were generally high, although well‐developed mesoscale residual currents were important, controlling dispersal pathways offshore. Vertical migration strategies, synchronized either with the tide (tidal stream transport) or with the Earth's rotation (diel transport), enabled more larvae to remain close to the coast, and simulations indicated higher retention than for passive larvae. However, the probability of connectivity with other populations and potential survivorship was greater for tidal strategies than for passive (although passive transport populated more distinct areas albeit in smaller proportions, as more larvae remained stranded offshore), or diel, where larvae remained close to their release location.

Transcriptomics of coping strategies in free‐swimming Lepeophtheirus salmonis (Copepoda) larvae responding to abiotic stress - Ben J. G. Sutherland; Stuart G. Jantzen; Motoshige Yasuike; Dan S. Sanderson; Ben F. Koop; Simon R. M. Jones (Molecular Ecology, 2012)
The salmon louse Lepeophtheirus salmonis is a marine ectoparasite of wild and farmed salmon in the Northern Hemisphere. Infections of farmed salmon are of economic and ecological concern. Nauplius and copepodid salmon lice larvae are free‐swimming and disperse in the water column until they encounter a host. In this study, we characterized the sublethal stress responses of L. salmonis copepodid larvae by applying a 38K oligonucleotide microarray to profile transcriptomes following 24 h exposures to suboptimal salinity (30–10 parts per thousand ( ‰ )) or temperature (16–4 °C) environments. Hyposalinity exposure resulted in large‐scale gene expression changes relative to those elicited by a thermal gradient. Subsequently, transcriptome responses to a more finely resolved salinity gradient between 30 ‰ and 25 ‰ were profiled. Minimal changes occurred at 29 ‰ or 28 ‰ , a threshold of response was identified at 27 ‰ , and the largest response was at 25 ‰. Differentially expressed genes were clustered by pattern of expression, and clusters were characterized by functional enrichment analysis. Results indicate larval copepods adopt two distinct coping strategies in response to short‐term hyposaline stress: a primary response using molecular chaperones and catabolic processes at 27 ‰ ; and a secondary response up‐regulating ion pumps, transporters, a different suite of chaperones and apoptosis‐related transcripts at 26 ‰ and 25 ‰ . The results further our understanding of the tolerances of L. salmonis copepodids to salinity and temperature gradients and may assist in the development of salmon louse management strategies.

Genomic Resources for Sea Lice: Analysis of ESTs and Mitochondrial Genomes - Motoshige Yasuike; Jong Leong; Stuart G. Jantzen; Kristian R. von Schalburg; Frank Nilsen; Simon R. M. Jones; Ben F. Koop (Marine Biotechnology, 2012)

Global threats to pinnipeds - Kit M. Kovacs; Alex Aguilar; David Aurioles; Vladimir Burkanov; Claudio Campagna; Nick Gales; Tom Gelatt; Simon D. Goldsworthy; Simon J. Goodman; Greg J. G. Hofmeyr; Tero Härkönen; Lloyd Lowry; et al. (Marine Mammal Science, 2012)

Effect of body tilt angle on fatigue and EMG activities in lower limbs during cycling - Mikel Egaña; Katie Ryan; Stuart A. Warmington; Simon Green (European Journal of Applied Physiology, 2010)

Structural characterisation of neutrophil glycans by ultra sensitive mass spectrometric glycomics methodology - Ponnusamy Babu; Simon J. North; Jihye Jang-Lee; Sara Chalabi; Kathryn Mackerness; Sean R. Stowell; Richard D. Cummings; Sara Rankin; Anne Dell; Stuart M. Haslam (Glycoconjugate Journal, 2009)

Quantification of Extinction Risk: IUCN's System for Classifying Threatened Species - GEORGINA M. MACE; NIGEL J. COLLAR; KEVIN J. GASTON; CRAIG HILTON‐TAYLOR; H. RESIT AKÇAKAYA; NIGEL LEADER‐WILLIAMS; E.J. MILNER‐GULLAND; SIMON N. STUART (Conservation Biology, 2008)
The International Union for Conservation of Nature (IUCN) Red List of Threatened Species was increasingly used during the 1980s to assess the conservation status of species for policy and planning purposes. This use stimulated the development of a new set of quantitative criteria for listing species in the categories of threat: critically endangered, endangered, and vulnerable. These criteria, which were intended to be applicable to all species except microorganisms, were part of a broader system for classifying threatened species and were fully implemented by IUCN in 2000. The system and the criteria have been widely used by conservation practitioners and scientists and now underpin one indicator being used to assess the Convention on Biological Diversity 2010 biodiversity target. We describe the process and the technical background to the IUCN Red List system. The criteria refer to fundamental biological processes underlying population decline and extinction. But given major differences between species, the threatening processes affecting them, and the paucity of knowledge relating to most species, the IUCN system had to be both broad and flexible to be applicable to the majority of described species. The system was designed to measure the symptoms of extinction risk, and uses 5 independent criteria relating to aspects of population loss and decline of range size. A species is assigned to a threat category if it meets the quantitative threshold for at least one criterion. The criteria and the accompanying rules and guidelines used by IUCN are intended to increase the consistency, transparency, and validity of its categorization system, but it necessitates some compromises that affect the applicability of the system and the species lists that result. In particular, choices were made over the assessment of uncertainty, poorly known species, depleted species, population decline, restricted ranges, and rarity; all of these affect the way red lists should be viewed and used. Processes related to priority setting and the development of national red lists need to take account of some assumptions in the formulation of the criteria.

Order parameter coupling in leucite: a calorimetric study - Helen Newton; Stuart A. Hayward; Simon A. T. Redfern (Physics and Chemistry of Minerals, 2008)

MicroCT Analysis of Symphyseal Ontogeny in Archaeolemur - Matthew J. Ravosa; Stuart R. Stock; Elwyn L. Simons; Ravinder Kunwar (International Journal of Primatology, 2007)

Use and misuse of the IUCN Red List Criteria in projecting climate change impacts on biodiversity - H. RESIT AKÇAKAYA; STUART H. M. BUTCHART; GEORGINA M. MACE; SIMON N. STUART; CRAIG HILTON‐TAYLOR (Global Change Biology, 2006)
Recent attempts at projecting climate change impacts on biodiversity have used the IUCN Red List Criteria to obtain estimates of extinction rates based on projected range shifts. In these studies, the Criteria are often misapplied, potentially introducing substantial bias and uncertainty. These misapplications include arbitrary changes to temporal and spatial scales; confusion of the spatial variables; and assume a linear relationship between abundance and range area. Using the IUCN Red List Criteria to identify which species are threatened by climate change presents special problems and uncertainties, especially for shorter‐lived species. Responses of most species to future climate change are not understood well enough to estimate extinction risks based solely on climate change scenarios and projections of shifts and/or reductions in range areas. One way to further such understanding would be to analyze the interactions among habitat shifts, landscape structure and demography for a number of species, using a combination of models. Evaluating the patterns in the results might allow the development of guidelines for assigning species to threat categories, based on a combination of life history parameters, characteristics of the landscapes in which they live, and projected range changes.

Glycomic studies of Drosophila melanogaster embryos - Simon J. North; Kate Koles; Caleb Hembd; Howard R. Morris; Anne Dell; Vladislav M. Panin; Stuart M. Haslam (Glycoconjugate Journal, 2006)

Effect of posture on high-intensity constant-load cycling performance in men and women - Mikel Egaña; Simon Green; Eoin J. Garrigan; Stuart Warmington (European Journal of Applied Physiology, 2006)

Species Review of Amphibian Extinction Risks in Madagascar: Conclusions from the Global Amphibian Assessment - FRANCO ANDREONE; JOHN E. CADLE; NEIL COX; FRANK GLAW; RONALD A. NUSSBAUM; CHRISTOPHER J. RAXWORTHY; SIMON N. STUART; DENIS VALLAN; MIGUEL VENCES (Conservation Biology, 2005)
We assessed the extinction risks of Malagasy amphibians by evaluating their distribution, occurrence in protected areas, population trends, habitat quality, and prevalence in commercial trade. We estimated and mapped the distribution of each of the 220 described Malagasy species and applied, for the first time, the IUCN Red List categories and criteria to all species described at the time of the assessment. Nine species were categorized as critically endangered, 21 as endangered, and 25 as vulnerable. The most threatened species occur on the High Plateau and/or have been subjected to overcollection for the pet trade, but restricted extent of occurrence and ongoing habitat destruction were identified as the most important factors influencing extinction threats. The two areas with the majority of threatened species were the northern Tsaratanana‐Marojejy‐Masoala highlands and the southeastern Anosy Mountains. The current system of protected areas includes 82% of the threatened amphibian species. Of the critically endangered species, 6 did not occur in any protected area. For conservation of these species we recommend the creation of a reserve for the species of the Mantella aurantiaca group, the inclusion of two Scaphiophryne species in the Convention on the International Trade in Endangered Species Appendix II, and the suspension of commercial collecting for Mantella cowani. Field surveys during the last 15 years reveal no pervasive extinction of Malagasy amphibians resulting from disease or other agents, as has been reported in some other areas of the world.

Habitat Suitability Models and the Shortfall in Conservation Planning for African Vertebrates - CARLO RONDININI; SIMON STUART; LUIGI BOITANI (Conservation Biology, 2005)
Ongoing loss of biodiversity requires identifying large‐scale conservation priorities, but the detailed information on the distribution of species required for this purpose is often missing. We present a systematic reserve selection for 1223 African mammals and amphibians in which habitat suitability models are used as estimates of the area occupied by species. In the framework of the World Conservation Union (IUCN) Global Amphibian Assessment and IUCN Global Mammal Assessment, we collected the geographic range (extent of occurrence) and habitat preferences for each species. We used the latter to build species‐specific habitat suitability models inside geographic ranges, and for 181 species we verified the models by comparing suitability levels to presence‐absence data collected in the field. We then used the suitable areas as estimators of the area of occupancy and compared the results of systematic reserve selection based on geographic ranges to those based on estimated areas of occupancy. Our results showed that the reserve system would need a 30‐100% expansion to achieve minimal conservation targets, concentrated in the tropics, where species richness reaches a maximum. Comparative analyses revealed that using geographic ranges, which overestimate the area occupied by species, underestimates the total amount of area that needs to be conserved. The area selected for conservation doubled when we used the estimated area of occupancy in place of the geographic ranges. This happened because the suitable areas potentially occupied by each species overlapped less than their geographic ranges. As a result, any given protected area contained fewer species than predicted by the analysis of ranges. Because species are more specialized than our estimates of distribution based on extent of occurrence suggest, we propose that this is a general effect in systematic conservation planning.

Arabidopsis mutants that suppress the phenotype induced by transgene-mediated expression of cauliflower mosaic virus (CaMV) gene VI are less susceptible to CaMV-infection and show reduced ethylene sensitivity - Chiara Geri; Andrew J. Love; Edi Cecchini; Stuart J. Barrett; Janet Laird; Simon N. Covey; Joel J. Milner (Plant Molecular Biology, 2004)

Response to A. Henderson-Sellers and K. McGuffie - Simon Shackley; Peter Young; Stuart Parkinson (Climatic Change, 1999)

Uncertainty, Complexity and Concepts of Good Science in Climate Change Modelling: Are GCMs the Best Tools? - Simon Shackley; Peter Young; Stuart Parkinson; Brian Wynne (Climatic Change, 1998)

The mouse Chromosome 7 distal imprinting domain maps to G-bands F4/F5 - Colin V. Beechey; Simon T. Ball; K. M. Stuart Townsend; Janet Jones (Mammalian Genome, 1997)

The 26S-proteasome: regulation and substrate recognition - Simon Dawson; Richard Hastings; Katsuhiko Takayanagi; Stuart Reynolds; Peter Løw; Michael Billett; R. John Mayer* (Molecular Biology Reports, 1997)